Autosomal genome-wide analysis of diversity, adaptation and morphological traits in African indigenous sheep - Ahbara, Abulgasim (2020)
Since their domestication in the Near East approximately 10,000 years ago, sheep have adapted to a wide spectrum of geographic, ecosystems and management regimes due to their easy handling, manageable body size and better adaptability to variable biotic and abiotic stress factors such as feed shortages and extreme climatic conditions. African indigenous sheep, as are global sheep, originated in the Near East. They arrived, in the first instance, in North Africa via the Isthmus of Suez by the seventh millennium before present. These sheep were of thin-tail type and their dispersion southwards into the wider eastern Africa followed possibly the Nile river valley and the Red Sea coastline. The second wave brought fat-tail sheep into North and Northeast Africa via two entry points, the Isthmus of Suez and the Horn of Africa across the strait of Bab-el-Mandeb, respectively. The fat-rump sheep are a recent introduction and represent the third wave of arrival and dispersal of the species into eastern Africa. Consequently, the phenotypic variation within and among these sheep populations could be explained by differences in their ancestral origins, migratory history and local natural and human-driven selection. Sheep represents one of the most economically important livestock species in Africa, playing an important role to resource-poor farmers by providing a wide range of products and services (e.g. meat, milk, skin, hair, and manure for cash, security, gifts and religious rituals), and a form of savings and investments. However, their diversity level is likely shrinking and urgent action is required to conserve the indigenous breeds. The dependency of African agro-pastoral societies on sheep products likely co-evolved with the wide range of environmental adaptability and productivity traits present today in African indigenous sheep following natural and human-mediated selection. This work aimed to provide a comprehensive overview of genome-wide diversity, population structure and signatures of adaptive divergence of African indigenous sheep populations through the analysis of Illumina Ovine SNP50 Genotyping BeadChip and whole-genome resequencing data. In Chapter 2, we investigate the autosomal genome-wide profiles of 11 Ethiopian indigenous sheep populations using the Illumina Ovine 50K SNP BeadChip assay. Sheep from the Caribbean, Europe, Middle East, China, and western, northern and southern Africa were included to address globally, the genetic variation and history of Ethiopian sheep. Population relationship and structure analysis separated Ethiopian indigenous fat-tail sheep from their North African and Middle Eastern counterparts. It indicates two main genetic backgrounds and supports two distinct genetic histories for African fat-tail sheep. Within Ethiopian sheep, our results show that the short fat-tail sheep do not represent a monophyletic group. Four genetic backgrounds occur in Ethiopian indigenous sheep but at different proportions among the fat-rump and the long fat-tail sheep from western and southern Ethiopia. The Ethiopian fat-rump sheep share a genetic background with Sudanese thin-tail sheep. Genome-wide selection signature analysis identified putative candidate regions spanning genes influencing growth traits and fat deposition (NPR2, HINT2, SPAG8, INSR), development of limbs and skeletal structure, and tail formation (ALX4, HOXB13, BMP4), the occurrence and morphology of horns (RXFP2) and response to heat stress (DNAJC18). These findings suggest that the Ethiopian fat-tail sheep represent a uniquely admixed but distinct genepool that presents an important resource for understanding the genetic control of skeletal growth, fat metabolism and associated physiological processes. In Chapter 3, we generated and analyzed whole-genome data from 60 long fat-tail, 32 short fat-tail and 38 fat-rump sheep from Ethiopia and Libya (∼30x coverage) as well as 20 thin-tail sheep from Sudan (∼10x coverage). Overall, 34.8 million high-quality single nucleotide polymorphisms were identified and used to assess within and among population-level genome diversity. The results from this chapter were in close agreement with those reported in Chapter 2. The overall results are in line with the archeological history of African sheep relating to their proposed entry points into, and subsequent dispersal across the continent. The Libyan sheep population displays a high level of genetic variation combined with lower inbreeding values and effective population sizes (Ne), a consequence, most likely of the random mating breeding applied by the owners. Further genome-wide analysis including thin-tail sheep from Ethiopia including thin and fat-tail sheep from West, North and South Africa will provide a continent-wide comprehensive overview of the genome diversity of African indigenous sheep. In Chapter 4, using the whole-genome sequences, we identify candidate genome regions and genes associated with adaptation to environmental challenges and tail morphology in African sheep representing the different introduction events of the species on the continent. Based on the population relationship and structure analysis (Chapter 3), the study populations were initially clustered into four groups: Ethiopian fat-rump (ET_G1), Ethiopian long fat-tail (ET_G2), Libyan long fat-tail (LB) and Sudanese thin tail (SD) sheep. These groups represent sheep reared at sea level (< 50 m above sea level (asl)) (LB), in a desert environment (SD) (< 1000 m asl) and at higher altitudes (> 1300 m asl) (ET_G1 and ET_G2). Following morphological characterization of the caudal vertebrae, these populations were further categorized into two groups: long- (ET_G2 and SD) and short-tailed (ET_G1 and LB) sheep populations. Candidate regions associated with environmental adaptation and tail morphology were identified with three selection scan indexes (ZHp, ZFST and XP-EHH), using 34 million autosomal SNPs. Many candidate genes under selection were identified including; the salt-sensitivity related gene (PLEKHA7) in Libyan sheep, the hypoxia associated gene (EGLN1) in Ethiopian sheep, the HOXB13 gene contrasting long- and short-tailed sheep and ALOX12 a candidate gene associated with fat deposition. These most likely are candidates encoding the unique adaptations of African sheep to diverse environments and tail phenotypes. In conclusion, our results have provided novel insights into sheep genomic adaptations to extreme environments and they illustrate the impact that environmental challenges may have had on the tail morphology of African sheep. They offer a valuable repository of new information for future research on indigenous sheep breeding in response to current and future climatic challenges. Although the results augment archeological findings relating to sheep dispersal into and across the African continent, future genome-wide analysis including thin-tail sheep from Ethiopia as well as thin- and fat-tail sheep from western, northern and southern Africa will provide a comprehensive continent-wide insight on the genome diversity of African sheep. Furthermore, functional genomic and association studies, supported with precise phenotypic recording on larger samples sizes, will be necessary to identify the causative mutations in the candidate genes identified in this study and using genome-editing techniques further validate their functional significance. To the best of our knowledge, this is the first study that has assessed the genome profiles and dynamics of African indigenous sheep using both SNP Chip genotypes and whole-genome resequencing in the same populations. Additionally, this may be the first study to comprehensively identify such a repertoire of adaptive candidate genes in African indigenous sheep. This study, therefore, represents a major milestone in supporting breeding programs aimed at sustainable conservation of African sheep genetic resources.